Periodontics in the USA: An introduction. Issue 1 (18th December 2019) - Ryder, Mark I.
Abstract: The United States continues to be an incubator for new concepts and approaches to the diagnosis, treatment, and prevention of periodontal diseases. This volume of Periodontology 2000 presents some of these newer areas of research and paradigms that have emerged in the United States from both long‐established and new investigators. These areas include: (1) more comprehensive approaches to assessing the total periodontal microbiome, including bacteria, viruses, and fungi, and their interactions with both the local and systemic inflammatory and immune responses, as well as with other oral and systemic conditions and diseases; (2) new developments for a more comprehensive characterization of the patient genome, transcriptome, and proteome profiles and the role of these profiles in periodontal disease pathogenesis; (3) new developments in nonsurgical approaches to periodontal diseases, including broad‐based lines of attack using natural antimicrobials and host‐modulation therapies and more focused approaches that target specific interactions in the host response; and (4) new big data analysis, machine learning, and imaging approaches, both for understanding the pathogenesis of periodontal diseases and for developing improved risk‐assessment tools and better treatment outcomes.